Transforming properties of the cottontail rabbit papillomavirus oncoproteins Le6 and SE6 and of the E8 protein. - Harry, J B (1996)
Cottontail rabbit papillomavirus induces on cottontail and domestic rabbits papillomas which progress at a high frequency to carcinoma. The virus encodes three transforming proteins; one is translated from open reading frame (ORF) E7 and binds the retinoblastoma protein, and two, LE6 and SE6, are translated from the first and second ATGs of ORF E6, respectively. Here we show that neither of the E6 proteins coprecipitated with p53 in vitro, nor did they bind to a recently identified E6-binding protein (J. J. Chen, C. E. Reid, V. Band, and E. Androphy, Science 269:529-531, 1995). This protein was shown to bind to the E6 proteins of the high-risk human papillomairus types 16 and 18 but not to the low-risk human papillomavirus types VI and II. In-frame deletions cloned into the pZipNeo vector were used to identify structural features of SE6 and LE6 important for transformation of NIH 3T3 cells. Three deletions covering the amino-terminal half of SE6 did not transform cells. In two of the three deletions, two Cys-X-X-Cys motifs were deleted, each deletion preventing the formation of one of the potential small Zn fingers of SE6. Among the LE6 deletions, only one had a reduced transformation efficiency, while seven transformed cells at least as efficiently as wild-type LE6. In each of three of these seven mutants, two Cys-X-X-Cys motifs were deleted. None of the three amino acid deletions which abolished transformation by SE6 reduced transformation by LE6. Furthermore, transformation did not correlate with the level of SE6 or LE6 proteins detectable. ORF E8 colinear with ORF E6, which could generate a 50-amino-acid protein with a hydrophobic segment, did not transform cells when cloned into the pZipNeo vector. However, mutation of the E8 ATG, which did not alter the amino acid sequence of LE6, increased transformation by LE6 without affecting the level of LE6 expression. The data suggest that transformation by the E6 proteins is not mediated by interfering with p53 function or through binding to the E6-binding protein. Furthermore, different structural features are important to maintain transformation functions and protein stability of LE6 and SE6. Finally, E8 seems not to be a transforming protein but rather appears to modulate transformation bv LE6.